Repertoires of learned vocal signals: how do they originate, and are they adaptive? - Gammon, David E., author; Baker, Mike, advisor; Bjostad, Lou, committee member; Hufbauer, Ruth, committee member; Packard, Gary, committee member (Colorado State University. Libraries, 2004)
Two patterns are commonly found in studies of birdsong: individuals sing multiple versions of the song (i.e., they have a 'repertoire' of 'song types') and populations show geographic variation in the acoustic structure of songs (i.e., the songs of different locations sound different). In contrast, most black-capped chickadees (Poecile atricapillus) across North America share a simple 'fee-bee' song type that does not vary geographically. Repertoires and small-scale geographic variation have been found in only a few regions across their range such as Fort Collins, Colorado. I described the singing behavior of Fort Collins chickadees for the first time and tested the possible functional significance of the evolved song types. Fort Collins chickadees sing three song types that are acoustically distinct from the continental song type and from each other. Acoustic structure for each song type varied geographically in the area surrounding Fort Collins, and acoustic variations corresponded to the acoustic variation present in the songs of individual juveniles at the time of natal dispersal, showing that inaccurate learning can account for geographic variation. More acoustic variation existed within an area containing small discontinuous populations than within an area containing larger continuously distributed population, suggesting that isolation and/or high population turnover may increase the rate of song evolution. Furthermore, the song type most similar to the continental song type varied the least. I tested four popular hypotheses for possible functional significance associated with the novel repertoire and did not find support for any of them. When neighboring males were involved in a territorial singing contest, use of the same song type did not indicate the likelihood of conflict escalation. Additionally, song types were used in similar proportions when males communicated with females vs. other males. The abundance of song learning errors combined with the effects of isolation on song evolution appeared sufficient to account for the existence of repertoires and geographic variation without invoking an adaptive origin. I hypothesize that repertoires and geographic variation arose in most species as a consequence of the learning process rather than as an adaptation.
Keywords: zoology; ecology